1986
DOI: 10.1139/y86-013
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive changes in rat liver plasma membranes after chronic alcohol administration and its subsequent withdrawal

Abstract: Rat hepatic plasma membranes isolated after chronic alcohol feeding displayed a different buoyant density range with a significantly increased peak density value when spun isopycnically in a 30-50% sucrose (w/w) gradient. This change persisted up to 48 h of withdrawal from alcohol. Analysis of membrane lipids revealed certain significant alterations in the phospholipids as well as the fatty acyl composition in individual phospholipids of the experimental plasma membranes. During withdrawal of alcohol for 48 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…[55][56][57][58] Ethanol feeding has also been reported to alter membrane composition by inducing lipid peroxidation, 59,60 decreasing the biosynthesis of polyunsaturated fatty acids and changing membrane cholesterol and phospholipids. 61,62 However, how ethanol abuse may exert a nephrotoxic effect remains poorly understood. The presence of multiple abnormalities of renal tubules involving different segments indicates that exposure to ethanol may cause generalized tubular dysfunction.…”
Section: Biochemical and Molecular Basis Of Alcohol-induced Injury Tomentioning
confidence: 99%
“…[55][56][57][58] Ethanol feeding has also been reported to alter membrane composition by inducing lipid peroxidation, 59,60 decreasing the biosynthesis of polyunsaturated fatty acids and changing membrane cholesterol and phospholipids. 61,62 However, how ethanol abuse may exert a nephrotoxic effect remains poorly understood. The presence of multiple abnormalities of renal tubules involving different segments indicates that exposure to ethanol may cause generalized tubular dysfunction.…”
Section: Biochemical and Molecular Basis Of Alcohol-induced Injury Tomentioning
confidence: 99%
“…The importance of phospholipids for structure and integrity of cellular membranes suggests that many functional distur bances in alcoholism may be related to changes in phospholipid content and composition (3). Some stud ies showed that chronic alcohol intake resulted in the change of phospholipid content (11,25) but several studies have reported minor changes in phospholipid distribution (6,26,27). Resolution of the mechanisms underlying this change is complicated by changes of amount and duration of alcohol abuse.…”
Section: Methodsmentioning
confidence: 99%
“…One mechanism for cells to adapt to changing environmental conditions and/or membrane-active agents is to alter the lipid composition of their membranes [2,21,22], thereby altering membrane £uidity [6]. The membrane po-larization patterns of R. eutropha H850 cells grown on biphenyl suggested these cells adapted to the £uidizing e¡ect of biphenyl (Fig.…”
Section: Fatty Acid Composition Analysismentioning
confidence: 99%